Aplikasi Model TAM Terhadap Pengguna Layanan Internet Banking di Kantor Bank Jatim Cabang Situbondo - Joni Hendra; Ahmad Iskandar R (Ecobuss, 2016)
This study is a replica of a previous study conducted by Davis (1993). Perceived ease of used and perceived usefulness has an influence on attitude toward using, behavioral intention in use, and the actual usage. The research objective is; 1) to determine the influence of perceived easy of use to the attitude toward using intenet banking, 2) to determine the influence of perceived usefulness on attitude toward using internet banking. 3) to determine the influence of perceived usefulness on behavioral intention to use internet banking, 4) to determine the effect of the behavioral attitude toward using internet banking intention, 5) to determine the influence of behavioral intention to actual usage of internet banking. This study approach quantitative and associative with the construct of exogenous variables (Exogenous constructs) and a construct of Endogenous (Endogenous Constructs), so the method of data analysis used in this research is descriptive statistics. The test results for the construct validity of endogenous namely Perceived Ease of Use (PEOU) and endogenous constructs include Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention To Use (ITU) and Actual Usage System (ASU). Testing the hypothesis in this study using the technique SEM with AMOS, for testing; the effect of perceived ease of use of the perceived usefulness of internet banking, the effect of perceived ease of use of the attitude toward using internet banking, the impact of perceived usefulness on attitude toward using intenet banking, influence perceived usefulness of the behavioral intention to use internet banking, the influence of attitude toward using the behavioral intention internet banking, influence behavioral intention to actual usage of internet banking Keywords; Perceived Usefulness, Attitude Toward Using, Be havioral Intention To Use, and Actual Usage System